Clinical importance of preoperative fine needle aspiration biopsy and computed tomography in parotid gland masses - Sahin, Ender; Unlu, Ilhan; Unlu, Elif Nisa; Kaptan, Zeynep; Uzunkulaoglu, Hakki; Samim, Ethem Erdal; Tulaci, Kamil Gokce; Karadavut, Yunus (The European Research Journal, 2016)
Objectives. To determine the diagnostic value of fine needle aspiration biopsy (FNAB) and computed tomography (CT) in parotid masses in the basis of postoperative histopathological results. Methods. The records of 68 patients diagnosed with a parotid mass and undergone parotis surgery between November 2004 and February 2011 were evaluated retrospectively. Preoperative FNAB and the CT findings were compared with postoperative histopathological findings. Results. The study included 36 (58%) female and 26 (42%) male patients. The mean age of the patients was 43.9 years. No statistically significant difference was detected with regards to the performances of both FNAB and the CT (p=0.797). When it was evaluated in a detail, the performance of parotid CT(81.82%) to diagnose a mass in parotid gland was relatively better than FNAB (72.73%). The performance of FNAB (94.12%) to detect healthy ones was also greater than parotid CT (90.2%). Conclusion. We emphasize that preoperative FNAB and parotid CT should be performed to the patients with a parotid mass. The use of these two tests together can minimize the risk rate have been proved.